Africa's struggle for its art history of a postcolonial defeat - Savoy, Bénédicte 1972- (Princeton University Press, 2022)
"A major new history of how, between 1965 and 1985, African nations sought the restitution of works of art stolen during the colonial period, written by the most important and influential figure in the field"--
Keywords: Kolonialismus; Erstattung; Kunstraub; Afrika; Cultural property / Repatriation / Africa / History / 20th century; Cultural property / Protection / Africa / History / 20th century; Art, African; Museums / Acquisitions / Europe; Patrimoine culturel / Restitution / Afrique / Histoire / 20e siècle; Art africain; Musées / Acquisitions / Europe; Cultural property / Protection; Cultural property / Repatriation; Museums / Acquisitions; Africa; Europe; 1900-1999; History